AUDITING SYSTEMS AND FINANCIAL INFRACTIONS AMONGST GOVERNMENT ENTITIES IN KWARA STATE - Yusuf Alabi Olumoh; Mubaraq Sanni; Khadijat Omolara Babalola; Fatimah Zahra Uthman; Mubarak Olayiwola Sanni (Malete Journal of Accounting and Finance)
Financial infractions among government entities in Nigeria, such as embezzlement and misappropriation of public funds, have persisted largely due to ineffective auditing. This study aims to examine the impact of the auditing system on financial infractions by specifically assessing the impact of internal controls and financial audits on the prevention of financial infractions among government entities in Kwara State, Nigeria. The Primary data was collected from a population of 295 auditors across 76 MDAs in Kwara State. A descriptive survey research design was employed, involving 170 senior employees sampled from various MDAs in Kwara State through a random sampling technique. Data were collected through structured questionnaires and analyzed using Multiple Regression analysis. The findings revealed that internal controls have a positive impact on preventing financial infractions (β = 0.064, t = 2.848, p = 0.005), while financial audits have a negative and insignificant impact (β = -0.028, t = -0.306, p = 0.760). The study concluded that internal controls play a critical role in mitigating financial infractions within government entities in Kwara State, whereas financial audits appear to lack effectiveness in addressing these issues. The study recommended that the Kwara State Government entities enhance internal controls through regular assessments and training, and improve transparency in audit reporting to better mitigate financial infractions.